Revisiting Financial Volatility in the Indonesian Islamic Stock Market: GARCH – MIDAS Approach - Nevi Danila (Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Introduction/main objectives: The aim of this research is to study the impact of macroeconomic variables on the Indonesian Islamic stock market’s volatility. Background issues: To predict the stock market’s volatility, daily or high-frequency data has been applied to the model’s explanatory variables with the same data frequency. However, when it comes to the macroeconomic variables as volatility drivers, the data is low-frequency, such as weekly, monthly, or quarterly. The current study uses a model which treats the data equally. Novelty: This study employs the mixed data sampling (MIDAS) model, which allows data from multiple frequencies to be included in the same model. This model can combine daily stock returns’ data with monthly or quarterly macroeconomic data. Hence, this is the first paper to study the determinants of the volatility of Indonesia's Islamic stock index using GARCH-MIDAS. Research Methods: The Generalized Autoregressive Conditional Heteroscedasticity GARCH-MIDAS model captures the short-run from the long-term element of volatility; the findings show the asymmetry effect for the short-term element’s result. Finding/Results: Inflation does not influence long-term market volatility. Moreover, after the 2008 crisis, the study shows that inflation and short-term interest rates positively influenced market volatility. Conclusion: The positive effect of inflation suggests that stocks can function as inflation hedges for stock investors in the long run. Further, the positive impact of interest rates implies that Muslim investors use the conventional short-term interest rates as a benchmark for investment in Shari’ah-compliant instruments.